Genetic distance and phylogenetic relationships of some Echinostoma species (E. malayanum, E. revolutum, E. miyagawai) and Hypoderaeum conoideum (family Echinostomatidae) inferred from partial 28S rDNA sequence analysis - Hoa, Le Thanh; Khanh Linh, Pham Thi; Khue, Nguyen Thi; Roan, Do Thi; Kim Xuyen, Le Thi; Thanh Huong, Doan Thi (Vietnam Journal of Biotechnology, 2022)
Echinostomiasis is a neglected disease caused by the intestinal flukes (family Echinostomatidae, suborder Echinostomata) and is common in communities in Asian countries, such as India, Indonesia, the Philippines, China, Malaysia, Singapore, Korea, Japan, Thailand, Laos, Cambodia and Vietnam. The genetic markers from the nuclear ribosomal transcription units are commonly used in genetic studies and phylogenetic analyses. A portion of the 28S rDNA sequence (domains D1–D3, of 1062–1067 bp for the final use) was obtained from the zoonotic Echinostoma malayanum (strain E/Amala-EMI3-TH), E. revolutum (strain Erevo-MSD15-TH), E. miyagawai (Emiya-RED11-TH), and Hypoderaeum conoideum (Hcono-RED42-TH) species; and used to perform an alignment for genetic distance estimation and phylogenetic analysis. The alignment was performed using 62 strains of 42 species from 19 genera of the family Echinostomatidae, including Echinoparyphium, Echinostoma, Artyfechinostomum, Patagifer, Neoacanthoparyphium, Hypoderaeum, Echinoparyphium, Drepanocephalus, Euparyphium, Chaunocephalus, Neopetasiger, Ribeiroia, Cathaemasia, Rhopalias, Isthmiophora, Petasiger, Moliniella, Pegosomum, and Schistosoma (family Schistosomatidae). The genetic distance estimation among 16 strains/10 species has shown a low intra-specific divergence level between strains within the same species, such as E. miyagawai (0–0.10%), E. revolutum (0.10–0.50%), and H. conoideum (0–0.10%), while between strains within the same genus it was higher (normally over 1.0%) and among strains/species between genera it was the highest (3.06–4.12%). The 28S rDNA sequence analysis and phylogenetic relationship well supported the Echinostoma/ Artyfechinostomum malayanum intergeneric taxonomy and the topology indicated clear, well-supported positions of member species in different genera in the family Echinostomatidae of the suborder Echinostomata. More sensu lato samples of the genera, are required for sequencing, particularly those of zoonotic species in the five genera: Artyfechinostomum, Echinostoma, Hypoderaeum, Echinoparyphium, and Isthmiophora. The resultant mitochondrial and nuclear data obtained from these species will be a good source to use to clearly assess the taxonomic and generic relationships.